Effective team leadership for engineers - Wellington, Patricia; Foster, Niall (Stevenage : Institution of Engineering and Technology, 2009)
This book is a must for engineers who have just, or will soon, become team leaders. It is also an essential guide for more experienced team and project leaders who wish to brush up their skills and knowledge. No matter what type of team or project you are leading you will be provided with practical guidance in setting the direction, plus establishing targets, goals and purpose for a winning team. Getting the environment right for your team to flourish, including motivating performance, will be explored, as will the thorny question of how to manage conflict and underperformance and boost morale.
Includes bibliographical references and index.
Keywords: Leadership; Engineers